Molecular mechanisms and hormonal regulation underpinning morphological dormancy: a case study using Apium graveolens (Apiaceae) - Walker, Matthew; Pérez, Marta; Steinbrecher, Tina; Gawthrop, Frances; Pavlović, Iva; Novák, Ondřej; Tarkowská, Danuše; Strnad, Miroslav; Marone, Federica; Nakabayashi, Kazumi; Leubner-Metzger, Gerhard (The Plant journal, 2021)
Underdeveloped (small) embryos embedded in abundant endosperm tissue, and thus having morphological dormancy (MD) or morphophysiological dormancy (MPD), are considered to be the ancestral state in seed dormancy evolution. This trait is retained in the Apiaceae family, which provides excellent model systems for investigating the underpinning mechanisms. We investigated Apium graveolens (celery) MD by combined innovative imaging and embryo growth assays with the quantification of hormone metabolism, as well as the analysis of hormone and cell-wall related gene expression. The integrated experimental results demonstrated that embryo growth occurred inside imbibed celery fruits in association with endosperm degradation, and that a critical embryo size was required for radicle emergence. The regulation of these processes depends on gene expression leading to gibberellin and indole-3-acetic acid (IAA) production by the embryo and on crosstalk between the fruit compartments. ABA degradation associated with distinct spatiotemporal patterns in ABA sensitivity control embryo growth, endosperm breakdown and radicle emergence. This complex interaction between gibberellins, IAA and ABA metabolism, and changes in the tissue-specific sensitivities to these hormones is distinct from non-MD seeds. We conclude that the embryo growth to reach the critical size and the associated endosperm breakdown inside MD fruits constitute a unique germination programme.
Keywords: endosperm breakdown; Apium graveolens (celery); embryo growth; Apium; gibereliny; klíčení; Seeds; underdeveloped embryo; semena rostlinná; Gibberellins; Models, Biological; dormancy evolution; kyseliny indoloctové; vegetační klid; Indoleacetic Acids; regulátory růstu rostlin; biologické modely; morphological dormancy; auxin transport; endosperm; Biological Transport; Plant Dormancy; Gene Expression Regulation, Plant; biologický transport; Plant Growth Regulators; Endosperm; regulace genové exprese u rostlin; Germination; ABA-gibberellin balance